Influence of spray-drying and freeze-drying on anthocyanins and antioxidant activities of Phlebopus colossus (R. Heim) Singer powder - Liaotrakoon, Wijitra; Liaotrakoon, Vachiraya (Journal of Food Technology, Siam University, 2021)
This research aims to study the preparation conditions of bolete mushroom (Phlebopus colossus (R. Heim) Singer) extract, to examine the spray-drying and freeze -drying affect the anthocyanin and antioxidant activity of the bolete powder, and to monitor the quality changes during storage. Four preparation conditions, i.e., (1) blending with water at room temperature for 5 min, (2) blending with hot water for 5 min, (3) boiling for 15 min then blending with water at room temperature for 5 min, and (4) boiling for 15 min then blending with hot water for 5 min were performed. It was found that the extraction by method 1 provided the highest total soluble solids, anthocyanin, and antioxidant activity than the others (p<0.05). After that, the extracts were dried with spray dryer at inlet temperatures of 165 and 200 ˚C, and freeze drier using 5, 10 and 15% of maltodextrin. The powder with 5% maltodextrin showed the highest anthocyanin, phenolic, and antioxidant activity followed by 10 and 15%, respectively (p<0.05). On the other hand, the inlet temperatures had no significant effect on the properties of the bolete mushroom powders (p>0.05), The anthocyanin and antioxidant activity of freeze-dried bolete mushroom powder were higher than spray-dried powder (p<0.05). Regrading to the quality changes during storage with aluminum foil and plastic bags at 7 and 25 ˚C for 60 days, the powder storage in an aluminum foil bags at 7°C ensured the highest antioxidant quality.